2017
DOI: 10.1016/j.compstruct.2016.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional nonlinear micro/meso-mechanical response of the fibre-reinforced polymer composites

Abstract: A three-dimensional multi-scale computational homogenisation framework is developed for the prediction of nonlinear micro/meso-mechanical response of the fibre-reinforced polymer (FRP) composites. Two dominant damage mechanisms, i.e. matrix elasto-plastic response and fibre-matrix decohesion are considered and modelled using a non-associative pressure dependent paraboloidal yield criterion and cohesive interface elements respectively. A linear-elastic transversely isotropic material model is used to model yarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…In order to perform this transformation, the yarns direction needs to be calculated at each of these points. In this paper, a similar approach based on the potential flow theory, as described in our previous publication [17,18,37], is used for the calculation of yarns' directions. Yarns are considered as pipes and the potential flow problem is solved through each of them in turn.…”
Section: Yarns Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to perform this transformation, the yarns direction needs to be calculated at each of these points. In this paper, a similar approach based on the potential flow theory, as described in our previous publication [17,18,37], is used for the calculation of yarns' directions. Yarns are considered as pipes and the potential flow problem is solved through each of them in turn.…”
Section: Yarns Directionsmentioning
confidence: 99%
“…Due to the multi-scale, complicated and heterogeneous nature of 3D-textile composites, computational homogenisation (CH) is the most appropriate computational framework for the calculation of their effective or homogenised properties [17,18]. These homogenised properties can then be used for the analysis of macro-level structure.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that damage initiation is mainly due to interfacial damage under both transverse tension and shear loadings and that the damage initiation under longitudinal shear load is mainly due to the damage of the epoxy matrix. Ullah et al [32] developed a computational homogenization framework to predict the nonlinear mechanical response of FRP composites. The accuracy and performance of the computational framework are demonstrated with a variety of numerical examples.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental mechanics-based approach adopted in this study for verifying the RVE concept is very general, while the technical literature usually focuses on determining the proper homogenization scheme as well as on the RVE shape and size to be used in specific homogenization-based computations on heterogeneous materials such as, for example, composite materials reinforced by fibers, random fibers, textures, or randomly distributed inclusions [15][16][17][18][19][20]. Regarding the specific application of optical methods to RVE analysis, it should be mentioned that digital image correlation was recently used for multiscale investigation on woven composites [21,22].…”
Section: Introductionmentioning
confidence: 99%